The Rhetoric of Imaginaries: How Creators, Ex-Creators, and Critics of Recent Media Technology Imagine the Future of Technological Transformation. An Analysis of Statements Made in Critical Documentaries from 2015–2021 - Kopecka-Piech, Katarzyna; Teichert, Jeannine (Roczniki Nauk Społecznych, 2025)
This study analyses future technological imaginaries by combining Aristotle’s three modes of expression and the rhetorical triangle with a modality matrix of rhetorical mappings of Raven and Elahi. The goal was to identify the narratives that shape the logos, ethos, and pathos of three groups of communicators in documentary films: creators, former creators, and critics of technologies. The study used a content analysis of the statements made by representatives of all three groups in eight critical documentaries on the future of technological development from 2015–2021. We extracted key categories for the logos, pathos and ethos of each speaker group. Most are dystopian. We argue that future research should critically rethink whether continuous observation of the tech elite from the sideline will do justice to the potential fulfillment of their prophecies.